2019
DOI: 10.3892/ijmm.2019.4249
|View full text |Cite
|
Sign up to set email alerts
|

The role of antimiR-26a-5p/biphasic calcium phosphate in repairing rat femoral defects

Abstract: Although miRNAs have been implicated in the osteogenic differentiation of stem cells, their role in bone repair and reconstruction in tissue-engineered bone grafts remains unclear. We previously reported that microRNA (miR)-26a-5p inhibited the osteogenic differentiation of adipose-derived mesenchymal stem cells (ADSCs), and that antimiR-26a-5p exerted the opposite effect. In the present study, the role of miR-26a-5p- and antimiR-26a-5p-modified ADSCs combined with biphasic calcium phosphate (BCP) scaffolds wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(18 citation statements)
references
References 57 publications
0
17
1
Order By: Relevance
“…This is indeed a very interesting finding, since Yan et al [ 115 ] reported an osteogenic differentiation of rat bone marrow stem cells due to miRNA-26a encapsulated into silica mesopores and Zhang et al [ 104 ] reported on the activation of osteoblastic activity of endogenous stem cells as a result from miRNA-26a loaded into cell-free 3D-printed scaffolds. The discrepancy in findings between the results reported by Yuan et al [ 117 ] and the other two studies might be due to the use of ADSCs in the former.…”
Section: Epigenetic Functionalization Of Biomaterials To Enhance Bcontrasting
confidence: 56%
See 1 more Smart Citation
“…This is indeed a very interesting finding, since Yan et al [ 115 ] reported an osteogenic differentiation of rat bone marrow stem cells due to miRNA-26a encapsulated into silica mesopores and Zhang et al [ 104 ] reported on the activation of osteoblastic activity of endogenous stem cells as a result from miRNA-26a loaded into cell-free 3D-printed scaffolds. The discrepancy in findings between the results reported by Yuan et al [ 117 ] and the other two studies might be due to the use of ADSCs in the former.…”
Section: Epigenetic Functionalization Of Biomaterials To Enhance Bcontrasting
confidence: 56%
“…In the repair of rat femoral defects, Yuan et al [ 117 ] seeded anti-miRNA-26a-5p-modified adipose-derived mesenchymal stem cells (ADSCs) on biphasic calcium phosphate (BCP) scaffolds, which resulted in an accelerated bone formation via the Wnt/Ca 2+ signaling pathway. This is indeed a very interesting finding, since Yan et al [ 115 ] reported an osteogenic differentiation of rat bone marrow stem cells due to miRNA-26a encapsulated into silica mesopores and Zhang et al [ 104 ] reported on the activation of osteoblastic activity of endogenous stem cells as a result from miRNA-26a loaded into cell-free 3D-printed scaffolds.…”
Section: Epigenetic Functionalization Of Biomaterials To Enhance Bmentioning
confidence: 99%
“…Among all included studies, bone defects were induced at various anatomical sites, involving the whole length of the femur, from the proximal femoral neck to the distal condyle. According to the descriptions of the surgical procedure, the authors summarized four major types of surgical methods used to induce femoral defects: (1) bone tunnel: cylindrical defect prepared by drilling, transversely involving either single or two cortical layers, or longitudinally along the femoral axis into the intramedullary cavity [ 29 , 30 , 31 , 32 , 33 ]; (2) cortical window: rectangular or rounded-rectangular defect involving one single cortex [ 34 , 35 , 36 ]; (3) segmental defect: complete segmental bone resection with parallel osteotomy [ 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]; and (4) wedge-shaped defect: removal of the bone block via opening wedge osteotomy [ 45 , 46 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, given the variability in defect sizes and animal status, there was also no specific consensus on the setting of follow-up for reference. Based on the information from the included studies, the authors recommend the selection of a critical gap size larger than 4 mm [ 43 , 44 ], a maximum follow-up of no less than 6 weeks for bone tunnel or cortical window models, and no less than 8−12 weeks for the osteotomy defects [ 29 , 30 , 31 , 32 , 34 , 35 , 36 , 38 , 39 , 40 ]. The impact of gender and defect size on the setting of follow-up periods might be further addressed in future animal studies.…”
Section: Discussionmentioning
confidence: 99%
“…In the process of intramembranous osteogenesis, MSCs directly differentiate into osteoblasts. Osteoblast differentiation is the primary step in the process of bone formation, and its regulatory pathways include a variety of signaling pathways such as bone morphogenetic protein (BMP), runt-related transcription factor 2 (RUNX2), transforming growth factor-beta (TGF-beta), and mitogenactivated protein kinase (MAPK) signaling pathway, as well as various transcription factors regulated by ncRNAs [22]. However, during endochondral osteogenesis, MSCs first differentiate into chondrocytes and form chondroid tissue, which is eventually replaced by bone tissue [23].…”
Section: Cells Differentiationmentioning
confidence: 99%